Cellular interactions between n-6 and n-3 fatty acids: a mass analysis of fatty acid elongation/desaturation, distribution among complex lipids, and conversion to eicosanoids. - D Rubin; M Laposata (Journal of Lipid Research, 1992)
The biologic effect of eicosanoids depends in large measure upon the relative masses in tissues of eicosanoids derived from the n-6 fatty acids, dihomogammalinolenic acid and arachidonic acid, and the n-3 fatty acid, eicosapentaenoic acid. Generation of this tissue balance is related to the relative cellular masses of these precursor fatty acids, the competition between them for entry into and release from cellular phospholipids, and their competition for the enzymes that catalyze their conversion to eicosanoids. In order to better understand these processes, we studied the cellular interactions of n-6 and n-3 fatty acids using an essential fatty acid-deficient, PGE-producing, mouse fibrosarcoma cell line, EFD-1. Unlike studies using cells with endogenous pools of n-6 and n-3 fatty acids, the use of EFD-1 cells enabled us to examine the metabolic fate of each family of fatty acids both in the presence and in the absence of the second family of fatty acids. Thus, the specific effects of one fatty acid family on the other could be directly assessed. In addition, we were able to replete the cells with dihomogammalinolenic acid (DHLA), arachidonic acid (AA), and eicosapentaenoic acid (EPA) of known specific activities; thus the masses of cellular DHLA, AA, and EPA, and their metabolites, PGE1, PGE2, and PGE3, respectively, could be accurately quantitated. The major findings of this study were: 1) n-6 fatty acids markedly stimulated the elongation of EPA to 22:5 whereas n-3 fatty acids inhibited the delta 5 desaturation of DHLA to AA and the elongation of AA to 22:4; 2) n-6 fatty acids caused a specific redistribution of cellular EPA from phospholipid to triacylglycerol; 3) n-3 fatty acids reduced the mass of DHLA and AA only in phosphatidylinositol whereas n-6 fatty acids reduced the mass of EPA to a similar extent in all cellular phospholipids; and 4) n-3 fatty acids caused an identical (33%) reduction in the bradykinin-induced release of PGE1 and PGE2, whereas n-6 fatty acids stimulated PGE3 release 2.3-fold. Together, these highly quantitative metabolic data increase our understanding of the regulation of both the cellular levels of DHLA, AA, and EPA, and their availability for eicosanoid synthesis. In addition, these findings provide a context for the effective use of these fatty acids in dietary therapies directed at modulation of eicosanoid production.